Engagement Aspects and Representational Functions in Quizizz Website as a Medium of English Language Instruction - Agis Andriani; Ila Yusrin Niamah; Yuyus Saputra (EDULANGUE, 2022)
Many studies have examined the role of the Quizizz website as a medium of English language instruction, especially for assessment, and found it to have positively impacted learners’ learning enthusiasm and engagement. However, few studies have examined the linguistic and visual aspects of Quizizz from a multimodal perspective. To fill this void, this study aimed to explore the engagement aspects and representational functions underlying certain parts of the Quizizz website from the multimodal lens. Using the content analysis approach, the data were taken from relevant documents and analyzed using the Systemic Functional Multimedia Discourse Analysis (SFMDA) framework (O'Halloran, 2008) with a focus on the representational meaning of visual and engagement taxonomy for each textual data. The findings showed that the Quizizz website entailed multimodal engagement taxonomy (disclaim, proclaim, entertainment, and attributes) and representational function (transactional, non-transactional, and covert). Specifically, the most dominant types were proclaiming and entertainment, encouraging students and entertaining them while undertaking quizzes. Nonetheless, the data in visual analysis displayed more covert taxonomy, which can reduce the students' thinking concepts that better reflect equal diversity in the form of multimodal.